Preparation method of multi-layer shell-core microcapsule / crosslinked polyethylene water tree self-repairing material modified by cooperation of plasma and coupling agent

By using a multi-layer putaway microcapsule modified with plasma synergistic coupling agent in crosslinked polyethylene cables, the limitations of traditional repair methods and the problem of degradation of insulation performance caused by aging of water trees is solved, and efficient self-repair effect is achieved and the life of the insulating material is extended.

CN119751931APending Publication Date: 2025-04-04HARBIN UNIV OF SCI & TECH

Patent Information

Application Number
CN202510011776.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-05
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively repair water tree defects in crosslinked polyethylene cables, and traditional repair methods require power outages and pressurization, which limits the actual application range, and the diffusion rate difference of the repair fluid leads to accumulation and blockage.

Method used

Multi-layer putaway microcapsules modified with plasma synergistic coupling agent were formed by the preparation of urea-formaldehyde resin prepolymer, the preparation of single-layer putaway microcapsules, the modification of plasma hydroxylated nanosilica and the modification of silane coupling agent to form a three-layer putaway microcapsules modified with plasma synergistic coupling agent. Combined with melt blending, cross-linking reaction and vacuum drying, cross-linking composite insulating material with self-healing ability was prepared.

Benefits of technology

It effectively reduces the agglomeration phenomenon of microcapsules, improves the dispersion and repair efficiency of microcapsules in the matrix, extends the operating life of the insulating material, and avoids the degradation of insulation performance caused by aging of water trees.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The crosslinked polyethylene cable has good performance and is widely applied to the fields of power grids and the like. Due to the action of long-time power frequency voltage, a cross-linked polyethylene cable insulating layer generates microdefects, and the water tree aging phenomenon is prone to occurring. Wherein some water branches gradually derive into electric branches under the action of a high-frequency electric field or overvoltage, so that electric field distortion is caused, and finally, a cable insulating layer is broken down. An existing microcapsule type self-repairing material is prone to agglomeration in a matrix, and the performance of the existing microcapsule type self-repairing material is greatly different from that of a matrix material, so that the performance of the self-repairing material is greatly reduced, and the repairing efficiency of a water tree is affected. Therefore, it is necessary to develop a multi-layer shell-core microcapsule / crosslinked polyethylene water tree self-repairing material modified by the plasma cooperating with the coupling agent, and a method for prolonging the service life of an insulating material is fundamentally explored.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the research field of insulating material self-repairing technology, and specifically relates to a preparation method of a plasma synergistic coupling agent modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-repairing material. Background Art

[0002] Cross-linked polyethylene cable has good insulation strength, heat resistance, corrosion resistance and mechanical properties. It is now widely used in urban distribution networks, industrial devices and large-capacity electrical equipment. However, during transportation and installation, it is inevitable that certain microscopic defects will be caused to the cable. During the subsequent operation, due to long-term heat and power frequency voltage, the insulation layer of the cross-linked polyethylene cable will also produce certain microscopic defects. Under the continuous action of moisture in the surrounding environment, the microscopic defects in the insulation layer are very prone to water tree aging. Water tree aging is a persistent polymer decomposition phenomenon in the material. Due to the intrusion of moisture into the insulation layer, water-containing dendritic channels are eventually formed under the combined action of electric field and degradation products. The interior is a chain of water-filled voids. A large number of void groups gather and intersect, and finally form a dendritic microchannel with a hydrophilic surface. Some of the water dendrites gradually evolve into electric dendrites under the action of high-frequency electric fields or overvoltages, causing electric field distortion and eventually causing the cable insulation layer to break down.

[0003] Although there is a technology to repair water tree defects in cross-linked polyethylene cables by injecting a repair agent to react with water, this method requires the cable to be powered off and pressurized, which seriously limits its practical use. At the same time, due to the difference in the diffusion rate of the molecules of the repair liquid components, the initial position is prone to accumulation and blockage of the repair liquid. Therefore, it is necessary to develop a microcapsule that can self-repair cross-linked polyethylene water trees to fundamentally explore ways to extend the operating life of insulating materials.

[0004] When microcapsules are doped into a cross-linked polyethylene matrix, the agglomeration of the microcapsules in the matrix and the performance of the microcapsules are significantly different from those of the cross-linked polyethylene material, resulting in a significant decrease in the performance of the self-healing material and affecting the water tree repair efficiency. The purpose of the present invention is to provide a method for preparing a multi-layer core-shell microcapsule / cross-linked polyethylene water tree self-healing material modified by a plasma synergistic coupling agent. The multi-layer core-shell microcapsules modified by a plasma synergistic coupling agent can reduce the agglomeration of the microcapsules and improve the performance of the microcapsules themselves, while the multi-layer core-shell structure can improve the repair efficiency. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies of the prior art. The present invention provides a method for preparing a plasma-synergistic coupling agent-modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material, which is an extension and development of the self-healing technology of insulating materials.

[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a plasma synergistic coupling agent modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-repairing material, including the preparation of urea-formaldehyde resin prepolymer, the preparation of single-layer core-shell microcapsules, plasma hydroxylated nano-silica, silane coupling agent KH550 modified hydroxylated nano-silica, preparation of urea-formaldehyde resin prepolymer surface-modified with nano-silica modified by plasma synergistic coupling agent, preparation of three-layer core-shell microcapsules modified by plasma synergistic coupling agent, and finally cooling, washing and drying to obtain microcapsules modified by plasma synergistic coupling agent for repairing cross-linked polyethylene water trees, and then melt blending, cross-linking reaction and vacuum drying to obtain a cross-linked polyethylene composite insulation material containing multilayer core-shell microcapsules modified by plasma synergistic coupling agent. Specifically comprising the following steps: (1) Preparation of urea-formaldehyde resin prepolymer: After urea is fully dissolved in deionized water, a 37% formaldehyde solution is added and mixed thoroughly. Triethanolamine is slowly added dropwise to the mixed solution to adjust the pH of the system to 8-9, and then the mixture is kept at 70°C for 60 minutes and cooled to room temperature after the reaction. The resulting colorless, transparent solution with a certain viscosity is the urea-formaldehyde resin prepolymer. (2) Preparation of single-layer core-shell microcapsules: The emulsifier sodium dodecylbenzene sulfonate, the catalyst linear alkylbenzene sulfonic acid and deionized water were fully mixed and stirred in a water bath at 40°C for 30 minutes. When the solution was white and milky, sodium hydroxide solution was slowly added to increase the pH of the system to 9-10. After the pH stabilized, ammonium chloride, resorcinol and urea-formaldehyde resin prepolymer were added to the solution in sequence. Then, citric acid was used to slowly reduce the pH of the solution to about 3.0, and the reaction was stirred at 60°C for 3 hours. After filtering, washing and drying, a powdered microcapsule sample with a single-layer core-shell structure was obtained. (3) Plasma hydroxylation of nano-silica: Hydroxylation of nano-silica is performed by performing room temperature air radio frequency plasma discharge on nano-silica, and the nano-silica is evenly spread on a quartz plate, and then the quartz plate is placed in a tube furnace. The tube furnace is evacuated using a vacuum system to maintain the air pressure at 10 Pa, and then the radio frequency power supply is turned on, the power is set to 250 W, and the processing time is 5 minutes. During the experiment, the relative humidity of the air in the tube furnace is 15%. (4) Silane coupling agent KH550 modified hydroxylated nano-silica: a certain amount of anhydrous ethanol was measured and added to a three-necked flask, and then a certain amount of plasma hydroxylated nano-silica was added and stirred at room temperature to make the nano-silica dispersed evenly in the anhydrous ethanol. Silane coupling agent KH550 was mixed with water in a certain proportion and stirred to fully hydrolyze the silane coupling agent until it cooled to room temperature and the stirring was stopped. The mixed solution of silane coupling agent and water was poured into the mixed solution of nano-silica and anhydrous ethanol, and condensed and refluxed for 3 hours at 70°C in a constant temperature magnetic stirrer. After the reaction was completed, it was washed and filtered with anhydrous ethanol until the filtrate was clear and transparent, and the filter cake was placed in a vacuum drying oven and dried at 70°C to obtain nano-silica particles modified by plasma synergistic coupling agent, which were then ground into powder. (5) Preparation of urea-formaldehyde resin prepolymer modified with nano-silica surface modified by plasma synergistic coupling agent: After urea is fully dissolved in deionized water, 37% formaldehyde solution and nano-silica modified by plasma synergistic coupling agent are added and mixed thoroughly. Triethanolamine is slowly added to the mixed solution to adjust the pH of the system to 8-9, and then the mixture is kept at 70°C for 60 minutes and cooled to room temperature after the reaction. The resulting white solution with a certain viscosity is the urea-formaldehyde resin prepolymer modified with nano-silica surface modified by plasma synergistic coupling agent. (6) Preparation of three-layer core-shell microcapsules modified by plasma synergistic coupling agent: The repair liquid dodecyltrimethoxysilane, the emulsifier sodium dodecylbenzenesulfonate and the single-layer core-shell microcapsules were fully mixed in deionized water, and stirred for 30 minutes in a water bath at 40°C, and then ammonium chloride, resorcinol, and urea-formaldehyde resin prepolymer modified with nano-silica surface modified by plasma synergistic coupling agent were added in sequence. After mixing and stirring for 3 minutes, the pH of the system was slowly lowered to about 3.0 with citric acid solution, and the pH adjustment process should be controlled within 10 to 20 minutes. After the pH of the solution stabilized, the temperature was raised to 60°C, and the reaction was kept warm for 3 hours under this condition. After filtering, washing and drying, a three-layer core-shell structure microcapsule sample modified by plasma synergistic coupling agent was obtained. (7) Melt blending: After setting the temperature of the torque rheometer to 110°C and the speed to 60 rpm, place the low-density polyethylene into the torque rheometer. After the low-density polyethylene is in a molten state and the torque is stable, add the antioxidant, microcapsule, and cross-linking agent in order. Take out the uniformly mixed composite material and cut it into small particles for later use. (8) Material melting: Make a corresponding mold according to the shape of the sample and calculate the mass of the required composite material. Set the temperature of the flat vulcanizer to 110°C, put the composite material in, heat for 15 minutes, and then increase the pressure every 5 minutes. Observe the pressure gauge in time and add pressure in time if the pressure is insufficient. (9) Cross-linking reaction: The temperature of another flat vulcanizer was set to 175°C, and the material of (8) was placed in the press. The pressure was increased to 15 MPa and the pressure was supplemented at any time. After heating for 35 minutes, the sample was fully cooled. (10) Vacuum drying: The temperature of the vacuum drying oven is set to 80° C. The cross-linked polyethylene is vacuum dried to obtain a plasma-synergistic coupling agent-modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material.

[0007] In the technical solution of the present invention: the mass ratio of the urea-formaldehyde resin wall material to the repair material core material in (2) is 2:1.

[0008] In the technical solution of the present invention: the particle size of the nano-silicon dioxide described in (3) is 20 nm.

[0009] In the technical solution of the present invention: the purpose of step (3) is to increase the hydroxyl content on the surface of nano-silicon dioxide and improve the bonding rate with the silane coupling agent KH550.

[0010] In the technical solution of the present invention: the purpose of step (4) is to increase the lipophilicity of nano-silicon dioxide so that the nano-silicon dioxide is evenly distributed on the surface of the urea-formaldehyde resin of the microcapsule shell, and at the same time, the microcapsules are evenly distributed in the cross-linked polyethylene matrix.

[0011] In the technical solution of the present invention: the purpose of increasing the pressure in (8) is to fully shape the material so that the impurity gas in the material can be fully discharged.

[0012] In the technical solution of the present invention: the purpose of step (10) is to reduce the influence of the cross-linking byproducts and residual stress inside the sample on the test.

[0013] Compared with the prior art, the advantages of the present invention are: (1) The repair fluid reacts with the catalyst to consume the moisture in the insulator, and the organic silicone resin generated after the reaction can fill the micropores, thereby eliminating the water tree and restoring the insulation performance of the water-tree aged cable. Organic silicone resin is not easy to decompose at high temperatures and has the characteristics of high pressure resistance and good insulation performance. Its performance is similar to that of cross-linked polyethylene, which effectively fills the water tree cavities. (2) The nano-silica modified by plasma synergistic coupling agent can be evenly distributed on the urea-formaldehyde resin shell of the microcapsule, reducing its agglomeration phenomenon. (3) The multilayer core-shell microcapsules modified by plasma synergistic coupling agent can make the microcapsules more evenly distributed in the cross-linked polyethylene matrix, improve the dispersibility of the microcapsules in the matrix, and reduce the occurrence of agglomeration. (4) The multilayer core-shell microcapsules can separate the repair liquid from the catalyst during the production process to ensure that the repair material does not react with water. At the same time, they can also ensure that the microcapsules do not come into contact with water when the microcapsule / cross-linked polyethylene self-healing material does not undergo water tree aging, thus avoiding ineffective reactions. (5) The multilayer core-shell structure of the microcapsules allows the microcapsules to be more specifically distributed in areas of the cable that are prone to water tree damage, and can respond more quickly when water tree aging occurs, thereby increasing both the repair speed and the repair rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is the infrared spectrum of nano-silicon dioxide before and after plasma treatment.

[0015] Figure 2 This is the lipophilicity diagram of nano-silica modified by silane coupling agent KH550 at different plasma treatment times.

[0016] Figure 3 1 is a plasma synergistic coupling agent modified three-layer core-shell microcapsule prepared in Embodiment 1, 2 is a single-layer core-shell microcapsule prepared in Comparative Example 1, and 3 is a pure wall material prepared in Comparative Example 2.

[0017] Figure 4 Insulation properties of multilayer core-shell microcapsule / cross-linked polyethylene composites modified with plasma synergistic coupling agents at different concentrations.

[0018] Figure 5 The water tree morphology diagram formed after the accelerated water tree aging experiment, Figure 1 is a water tree aging diagram of a cross-linked polyethylene material without microcapsules, and Figure 2 is a water tree aging diagram of a cross-linked polyethylene material doped with one percent of microcapsules prepared in the first embodiment.

[0019] Figure 6 1 is a schematic diagram of water tree aging repair of a cross-linked polyethylene material without microcapsules, and 2 is a schematic diagram of water tree repair of a cross-linked polyethylene material doped with one percent of microcapsules prepared in Embodiment 1.

[0020] Figure 7 Diagram of the plasma processing system.

[0021] Figure 8 This is the schematic diagram of the modification of nano-silica by silane coupling agent KH550.

[0022] Fig. 9 Schematic diagram of the internal structure of three-layer core-shell microcapsules modified with plasma synergistic coupling agent. DETAILED DESCRIPTION

[0023] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0024] Specific implementation method 1: This implementation method 1 is a method for preparing a multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material modified by plasma synergistic coupling agent, which is specifically completed according to the following steps: (1) Preparation of urea-formaldehyde resin prepolymer: 20 g of urea was dissolved in 60 g of deionized water, and then 20 g of 37% formaldehyde solution was added. Under magnetic stirring at 300-400 rpm, the pH of the system was adjusted to 8-9 with triethanolamine, and then the mixture was kept at 70°C for 60 minutes. Then the mixture was cooled to room temperature. The resulting colorless, transparent solution with a certain viscosity was the urea-formaldehyde resin prepolymer. (2) Preparation of the aqueous phase of the single-layer core-shell microcapsule: 1.5 g of the emulsifier sodium dodecylbenzene sulfonate, 20 g of the catalyst linear alkylbenzene sulfonic acid and 45 g of deionized water were mixed and stirred for 40 minutes at a speed of 500 rpm under mechanical stirring and a 40°C water bath. When the solution was white and milky, sodium hydroxide solution was slowly added dropwise to increase the pH of the system to 9-10. (3) Formation of single-layer core-shell microcapsules: Urea-formaldehyde resin prepolymer was added dropwise to the aqueous phase of the single-layer core-shell microcapsules, and 1 g of urea-formaldehyde resin curing agent ammonium chloride and 2 g of urea-formaldehyde resin water-resistant modifier resorcinol were added, and magnetic stirring was performed for 3 minutes. Then, 1 to 2 drops of defoaming agent n-octanol were added, and the pH of the solution was slowly reduced to about 3.0 with citric acid. The rotation speed was 600 rpm during acidification. Finally, the temperature was raised to 60°C, and the rotation speed was 500 rpm for stirring and reaction. During this period, the rotation speed was reduced to 450, 400, 350 to 300, and the time was 3 hours. (4) Drying treatment of single-layer core-shell microcapsules: After the reaction is completed, the product is filtered using a slow double-circle qualitative filter paper, washed three times with alcohol and deionized water respectively to remove impurities, and a filter cake is obtained. Finally, it is dried at 25°C for 48 hours to obtain a powdered single-layer core-shell microcapsule sample. (5) Plasma hydroxylation of nano-silica: Hydroxylated nano-silica was obtained by subjecting nano-silica to room temperature air radio frequency plasma discharge. 60 mg of nano-silica was evenly spread on a quartz plate, and then the quartz plate was placed in a tube furnace. The tube furnace was evacuated using a vacuum system to maintain the air pressure at 10 Pa, and then the radio frequency power supply was turned on and the power was set to 250 W. The treatment time was 5 minutes. During the experiment, the relative humidity of the air in the tube furnace was 15%. (6) Silane coupling agent KH550 modified hydroxylated nano-silica: 30 mL of anhydrous ethanol was measured and added to a three-necked flask, and then 1 g of plasma hydroxylated nano-silica was added and stirred at room temperature to make the nano-silica evenly dispersed in the anhydrous ethanol. Silane coupling agent KH550 was measured according to a liquid-to-solid ratio of 5:1 mL / g with nano-silica, and silane coupling agent KH550 was mixed with water in a ratio of 1:2 and stirred to fully hydrolyze the silane coupling agent until it cooled to room temperature and the stirring was stopped. The mixed solution of silane coupling agent and water was poured into the mixed solution of nano-silica and anhydrous ethanol, and condensed and refluxed in a constant temperature magnetic stirrer at 70°C for 3 hours. After the reaction was completed, it was washed with anhydrous ethanol and filtered until the filtrate was clear and transparent. The filter cake was placed in a vacuum drying oven and dried at 70°C to obtain nano-silica particles modified by plasma synergistic coupling agent, which were then ground into powder. (7) Preparation of urea-formaldehyde resin prepolymer modified with nano-silica surface modified by plasma synergistic coupling agent: 1g of nano-silica modified by plasma synergistic coupling agent and 20g of 37% formaldehyde solution were mixed and stirred, and then 20g of urea was added and dissolved with 60g of deionized water. Under magnetic stirring at 300-400rpm, the pH of the system was adjusted to 8-9 with triethanolamine, and then kept at 70°C for 60 minutes. Then cooled to room temperature. The obtained white solution with a certain viscosity is the urea-formaldehyde resin prepolymer modified with nano-silica surface modified by plasma synergistic coupling agent. (8) Preparation of the aqueous phase of plasma-coupling agent-modified three-layer core-shell microcapsules: 1.5 g of emulsifier sodium dodecylbenzene sulfonate, 16 g of repair liquid dodecyltrimethoxysilane, 4 g of single-layer core-shell microcapsules and 45 g of deionized water were mixed and stirred for 30 minutes at a speed of 400 rpm under mechanical stirring and a 40°C water bath. (9) Formation of plasma synergistic coupling agent modified three-layer core-shell microcapsules: The urea-formaldehyde resin prepolymer modified with nano-silica surface modified by plasma synergistic coupling agent was added dropwise to the aqueous phase of the three-layer core-shell microcapsules, and 1g of urea-formaldehyde resin curing agent ammonium chloride and 2g of urea-formaldehyde resin water-resistant modifier resorcinol were added, and magnetic stirring was performed for 3 minutes. Then, 1 to 2 drops of defoaming agent n-octanol were added, and the pH of the solution was slowly reduced to about 3.0 with citric acid. The rotation speed during acidification was 400 rpm. Finally, the temperature was raised to 60°C, and the rotation speed was 300 rpm for stirring and reaction for 3 hours. (10) Drying treatment of plasma synergistic coupling agent modified three-layer core-shell microcapsules: After the reaction is completed, the product is filtered using slow double-circle qualitative filter paper, washed three times with alcohol and deionized water respectively to remove impurities and obtain a filter cake. Finally, it is dried at 25°C for 48 hours to obtain a plasma synergistic coupling agent modified three-layer core-shell repaired cross-linked polyethylene water tree microcapsule sample. (11) Melt blending: Weigh 40 g of low-density polyethylene, 0.12 g of antioxidant, microcapsules accounting for 1%, 2%, 3%, 4% and 5% of the low-density polyethylene content respectively, and 0.72 g of cross-linking agent. Set the temperature of the torque rheometer to 110°C and the speed to 60 rpm, then put the low-density polyethylene into the torque rheometer, and add antioxidants, microcapsules and cross-linking agents in the order of running time of 1 minute, 3 minutes and 18 minutes. After 2 minutes after the cross-linking agent is added, the uniformly mixed composite material is taken out and cut into small particles for later use. (12) Material melting: A 4 cm × 4 cm × 4 mm square mold was made according to the shape of the sample. The mass of the required composite material was weighed to be 14.4 g. The temperature of the flat vulcanizer was set to 110 °C. The composite material wrapped with an iron plate and an oily polyester film was placed in the mold. After heating for 15 minutes, the pressure was increased every 5 minutes. The pressure gauge values ​​were 0 MPa, 5 MPa, 10 MPa, and 15 MPa. The pressure gauge was observed in time and the pressure was supplemented in time if it was insufficient. (13) Cross-linking reaction: The temperature of another flat vulcanizer was set to 175°C, and the material of (12) was placed in the press. The pressure was increased to 15 MPa and the pressure was replenished at any time. After heating for 35 minutes, the sample was fully cooled. (14) Vacuum drying: The temperature of the vacuum drying oven is set to 80° C. The prepared composite material is vacuum dried to obtain a plasma synergistic coupling agent modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material.

[0025] Comparative Example 1: The difference between this comparative example and Implementation Example 1 is that only steps (1) to (4) in Implementation Example 1 are performed to obtain the raw material.

[0026] Comparative Example 2: This comparative example differs from Implementation Example 1 in that only steps (1) to (4) in Implementation Example 1 are performed, and in step (2), no catalyst linear alkylbenzene sulfonic acid is added to obtain a raw material.

[0027] Figure 1 This is the infrared spectrum of nano-silicon dioxide before and after plasma treatment.

[0028] from Figure 1 It can be seen that after plasma treatment of nano-silica, the intensity of the hydroxyl characteristic peak of nano-silica is enhanced, which proves the effectiveness of plasma treatment.

[0029] Figure 2 This is the lipophilicity diagram of nano-silica modified by silane coupling agent KH550 at different plasma treatment times.

[0030] from Figure 2 It can be seen that with the increase of plasma treatment time, the lipophilicity of nano-SiO2 modified by silane coupling agent first increases and then decreases, reaching the maximum value at the 5th minute. This is because the air contains a certain amount of moisture, and the H2O molecules are dissociated into hydroxyl radicals in the plasma environment and grafted to the surface of nano-SiO2, thereby increasing its lipophilicity after modification. However, with the increase of plasma treatment time, the proportion of plasma etching increases, causing certain damage to the surface structure of nano-SiO2, reducing the number of hydroxyl groups on its surface, and then resulting in a decrease in the lipophilicity after modification.

[0031] Figure 3 1 is a plasma synergistic coupling agent modified three-layer core-shell microcapsule prepared in Embodiment 1, 2 is a single-layer core-shell microcapsule prepared in Comparative Example 1, and 3 is a pure wall material prepared in Comparative Example 2.

[0032] from Figure 3 It can be seen that the infrared absorption curves of Comparative Example 2, Implementation Example 1 and Comparative Example 1 are at 3353 cm -1 、1641cm -1 、1020cm -1 There are obvious infrared characteristic absorption peaks at 3353cm -1 The wide and strong absorption peak at 1641cm is the result of the hydrogen bonding effect in the molecular structure of urea-formaldehyde resin. -1 The 1020 cm-1 is the stretching vibration absorption peak of C=O in the amide bond of urea-formaldehyde resin, while the -1 The CO stretching vibration absorption peak at 1380cm is caused by the primary alcohol produced when the urea-formaldehyde resin is hydroxymethylated. These three infrared characteristic peaks prove that the embodiment 1, the comparative example 1 and the comparative example 2 have urea-formaldehyde resin wall materials. Compared with the comparative example 2, the embodiment 1 and the comparative example 1 have the same absorption peak at 1380cm -1 The infrared characteristic absorption peak appears, which is the vibration absorption peak of S=O, indicating that the embodiment 1 and the comparative example 1 contain the catalyst linear alkylbenzene sulfonic acid. Compared with the comparative example 1 and the comparative example 2, the embodiment 1 has a peak at 467 cm -1 and 1095cm -1 Infrared characteristic absorption peaks appeared at 467cm -1 The peak at 1095cm is the Si-O stretching vibration absorption peak. -1The peak at is the antisymmetric stretching vibration peak of Si-O-Si, indicating that the first embodiment contains the repair liquid dodecyltrimethoxysilane and the surface is attached with nano-silica modified by a plasma synergistic coupling agent.

[0033] Figure 4 Insulation properties of multilayer core-shell microcapsule / cross-linked polyethylene composites modified with plasma synergistic coupling agents at different concentrations.

[0034] from Figure 4 It can be seen that when the microcapsule content is 1%, the insulation performance of the composite material is not much different from that of the cross-linked polyethylene material.

[0035] Figure 5 The water tree morphology diagram formed after the accelerated water tree aging experiment, Figure 1 is a water tree aging diagram of a cross-linked polyethylene material without microcapsules, and Figure 2 is a water tree aging diagram of a cross-linked polyethylene material doped with one percent of microcapsules prepared in the first embodiment.

[0036] Depend on Figure 5 It can be seen that the length of the water tree branch is the length from the tip of the steel needle to the bottom of the water tree branch. In the figure, the length of the water tree branch 1 is significantly higher than the length of the water tree 2. This shows that the composite material prepared by the present invention has an inhibitory effect on the growth of water trees.

[0037] Figure 6 1 is a schematic diagram of water tree aging repair of a cross-linked polyethylene material without microcapsules, and 2 is a schematic diagram of water tree repair of a cross-linked polyethylene material doped with one percent of microcapsules prepared in Embodiment 1.

[0038] Depend on Figure 6 It can be seen that a series of water tree holes are generated in Figure 1 after water tree aging, while the water tree holes in Figure 2 are obviously filled. This proves that the embodiment of the present invention can repair water tree holes in time under the action of moisture after the water tree holes occur.

Claims

1. A method for preparing a plasma-synergistic coupling agent-modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material, characterized in that: Nano-silica treated with a plasma synergistic coupling agent is used as the outermost layer of the microcapsule, urea-formaldehyde resin is used as the wall material of the first and second layers, and a repair liquid and a catalyst are used as the core material. The capsule core is embedded in the capsule wall to form a three-layer coated multiple core-shell structure microcapsule. The polymerization reaction is regulated by changing the pH value of the emulsion to obtain a plasma synergistic coupling agent-modified three-layer core-shell microcapsule that can repair water tree damage in a cross-linked polyethylene material.

2. The microcapsule with a three-layer core-shell structure for repairing water trees of cross-linked polyethylene materials according to claim 1, characterized in that: The structural morphology is a three-layer core-shell microcapsule, the repair liquid and the catalyst are in the same whole, and the mass ratio of the repair liquid to the catalyst is determined to be 4:

1.

3. The microcapsule with a three-layer core-shell structure for repairing water trees of cross-linked polyethylene materials according to claim 1, characterized in that: The outermost layer of nano-silicon dioxide is synergistically treated with plasma and a coupling agent, the core material repair liquid of the repair material is dodecyltrimethoxysilane, and the catalyst is linear alkylbenzene sulfonic acid.

4. The microcapsule with a three-layer core-shell structure for repairing water trees of cross-linked polyethylene materials according to claim 1, characterized in that: The repair material core can react with moisture at room temperature to repair water trees.

5. A method for preparing a plasma-synergistic coupling agent-modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material, characterized in that: The following steps are involved: (1) Preparation of urea-formaldehyde resin prepolymer: After urea is fully dissolved in deionized water, a 37% formaldehyde solution is added and mixed thoroughly. Triethanolamine is slowly added dropwise to the mixed solution to adjust the pH of the system to 8-9, and then the mixture is kept at 70°C for 60 minutes and cooled to room temperature after the reaction. The resulting colorless, transparent solution with a certain viscosity is the urea-formaldehyde resin prepolymer. (2) Preparation of single-layer core-shell microcapsules: The emulsifier sodium dodecylbenzene sulfonate, the catalyst linear alkylbenzene sulfonic acid and deionized water were fully mixed and stirred in a water bath at 40°C for 30 minutes. When the solution was white and milky, sodium hydroxide solution was slowly added to increase the pH of the system to 9-10. After the pH stabilized, ammonium chloride, resorcinol and urea-formaldehyde resin prepolymer were added to the solution in sequence. Then, citric acid was used to slowly reduce the pH of the solution to about 3.0, and the reaction was stirred at 60°C for 3 hours. After filtering, washing and drying, a powdered microcapsule sample with a single-layer core-shell structure was obtained. (3) Plasma hydroxylation of nano-silica: Hydroxylation of nano-silica is performed by performing room temperature air radio frequency plasma discharge on nano-silica, and the nano-silica is evenly spread on a quartz plate, and then the quartz plate is placed in a tube furnace. The tube furnace is evacuated using a vacuum system to maintain the air pressure at 10 Pa, and then the radio frequency power supply is turned on, the power is set to 250 W, and the processing time is 5 minutes. During the experiment, the relative humidity of the air in the tube furnace is 15%. (4) Silane coupling agent KH550 modified hydroxylated nano-silica: a certain amount of anhydrous ethanol was measured and added to a three-necked flask, and then a certain amount of plasma hydroxylated nano-silica was added and stirred at room temperature to make the nano-silica dispersed evenly in the anhydrous ethanol. Silane coupling agent KH550 was mixed with water in a certain proportion and stirred to fully hydrolyze the silane coupling agent until it cooled to room temperature and the stirring was stopped. The mixed solution of silane coupling agent and water was poured into the mixed solution of nano-silica and anhydrous ethanol, and condensed and refluxed for 3 hours at 70°C in a constant temperature magnetic stirrer. After the reaction was completed, it was washed and filtered with anhydrous ethanol until the filtrate was clear and transparent, and the filter cake was placed in a vacuum drying oven and dried at 70°C to obtain nano-silica particles modified by plasma synergistic coupling agent, which were then ground into powder. (5) Preparation of urea-formaldehyde resin prepolymer modified with nano-silica surface modified by plasma synergistic coupling agent: After urea is fully dissolved in deionized water, 37% formaldehyde solution and nano-silica modified by plasma synergistic coupling agent are added and mixed thoroughly. Triethanolamine is slowly added to the mixed solution to adjust the pH of the system to 8-9, and then the mixture is kept at 70°C for 60 minutes and cooled to room temperature after the reaction. The resulting white solution with a certain viscosity is the urea-formaldehyde resin prepolymer modified with nano-silica surface modified by plasma synergistic coupling agent. (6) Preparation of three-layer core-shell microcapsules modified by plasma synergistic coupling agent: The repair liquid dodecyltrimethoxysilane, the emulsifier sodium dodecylbenzenesulfonate and the single-layer core-shell microcapsules were fully mixed in deionized water, and stirred for 30 minutes in a water bath at 40°C, and then ammonium chloride, resorcinol, and urea-formaldehyde resin prepolymer modified with nano-silica surface modified by plasma synergistic coupling agent were added in sequence. After mixing and stirring for 3 minutes, the pH of the system was slowly lowered to about 3.0 with citric acid solution, and the pH adjustment process should be controlled within 10 to 20 minutes. After the pH of the solution stabilized, the temperature was raised to 60°C, and the reaction was kept warm for 3 hours under this condition. After filtering, washing and drying, a three-layer core-shell structure microcapsule sample modified by plasma synergistic coupling agent was obtained. (7) Preparation of multilayer core-shell microcapsules / cross-linked polyethylene water tree self-healing materials modified by plasma synergistic coupling agent: low-density polyethylene is placed in a torque rheometer. After the low-density polyethylene is in a molten state and the torque is stable, antioxidants, microcapsules, and cross-linking agents are placed in order for melt blending. A corresponding mold is made according to the shape of the sample, and the mass of the required composite material is calculated. It is then pressurized using a flat vulcanizer and finally vacuum dried to obtain a multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material modified by plasma synergistic coupling agent.

6. The method for preparing the plasma synergistic coupling agent modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material according to claim 5, characterized in that: The plasma synergistic coupling agent modified nano-silica improves its dispersibility on the urea-formaldehyde resin wall material of the second layer of the microcapsule and enhances the performance of the microcapsule itself.

7. The method for preparing the plasma synergistic coupling agent modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material according to claim 5, characterized in that: After the nano-silica as the outermost layer of the microcapsule is treated with a plasma synergistic coupling agent, the dispersion of the microcapsule in the cross-linked polyethylene matrix is ​​improved and the occurrence of its agglomeration is reduced.

8. The method for preparing the plasma synergistic coupling agent modified multilayer core-shell microcapsule / cross-linked polyethylene water tree self-healing material according to claim 5, characterized in that: The multi-layer core-shell structure of microcapsules can improve both the repair rate and the repair speed.

Citation Information

Patent Citations

  • Method for improving dispersion of nano silica granules in polyimide resin

    CN101381514A

  • Plasma modification processing method of silicon dioxide nano powder surface at atmosphere pressure and normal temperature

    CN101417807A

  • Filler for self-repairing of insulating layer of cable and preparation method

    CN108299682A

  • Polyvinyl self-repairing composite medium with three-layer shell-core microcapsule gradient arrangement structure and preparation method of polyvinyl self-repairing composite medium

    CN117327336A

  • Crosslinked polyethylene self-repairing material with microcapsules in directional distribution under induction of direct-current electric field and preparation method of crosslinked polyethylene self-repairing material

    CN118772504A

Cited By

  • Rapid vulcanization crosslinking process suitable for 66kV-500kV crosslinked polyethylene insulated cable

    CN120173269A